TINGKAT INFEKSI SOIL-TRANSMITTED HELMINTH PADA ANAK SEKOLAH DASAR DI DATARAN TINGGI BADA, KECAMATAN LORE BARAT, KABUPATEN POSO, SULAWESI TENGAH - Rosmini Rosmini; Anis Nurwidayati (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2017)
Soil-transmitted helminths (STH) are a major public health problem in tropical and sub-tropical countries, also in Indonesia. STH’s infection were caused by nematode such as (ring worm, hook worm and whip worm. This infection affecting the physical growth and cognitive development in school age children. This study was aimed to assess the prevalence of STH infection among school children in Tuare and Lengkeka, West Lore District, Poso Regency, Central Sulawesi Province. This study was conducted with cross sectional design. The study was conducted in May 2016. Stool smple were collected from school children class 4 and 5 in Tuare and Lengkeka, then examined using Kato-Kat’z method. The results showed that infection of STH due to Ascaris worm were found inTuare and Lengkeka Village, which prevalence were 18.18% and 19.35%. Mix infection of Ascaris and hookworm were also found in both location with the prevalence were 9.09% and 6.45%. The infection of whip worm was only found in Tuare Village which prevalence was 4.55%. Based on the results can be concluded that the STH infection in Tuare and Lengkeka Village still remain high. The treatment of school children as well as behavioral counseling clean and healthy living were needed to be conducted in both village.